Implementing Social Labs in Addressing Radicalisation and Promoting Inter-Religious Dialogue - Leonora, Anna Maria; Nicolosi, Davide; Sodano, Pina; Nouri, Minalè (Italian Sociological Review, 2025)
Over recent decades, the European community has grappled with diverse forms of extremism and terrorism, exacerbated by economic crises, social divisions and the globalised nature of extremism. While most Preventing and Countering Violent Extremism (P/CVE) policies have targeted Islamic radicalisation, the approach has not fully addressed the nuances of different forms of extremism, including far-right ideologies. This paper argues for the inclusion of Social Labs as an innovative methodological approach from a sociological standpoint. The Social Lab methodology option, grounded in participatory action-research, places the community – here we refer to religious communities, religious leaders and inter-religious networks – as an integral part of the research and solution-creation process. Drawing on empirical research across Italy, Belgium and the Netherlands, this work combines qualitative tools like narrative interviews, focus groups, and working groups with inter-religious dialogue networks, aiming to foster localised, community-based solutions. The paper critically evaluates the analytical path of Social Labs in capturing the nuanced socio-economic and religious drivers of radicalisation and polarisation and explores its potential for preventing religious radicalisation at the grassroots level. The paper adds a critical layer by emphasising the need for methodological innovation in the form of Social Labs. It argues that Social Labs facilitate a more participative dynamics that can help in contextualising and ultimately countering extremism in its various forms. The paper concludes by presenting guidelines developed through Social Labs, aimed at fostering resilient communities and informing future policy and interventions.